O acordo comercial entre o Mercosul e a União Europeia: uma análise de acesso ao mercado europeu - Sardinha, Lucas Spazziani (Universidade Federal de São Carlos, 2022)
The objective of this work is to analyze the tariff elimination offer proposed by the European Union within the scope of the FTA signed with Mercosur in order to assess the possible effects of access to the European Union market by Mercosur countries. To this end, the tariffs imposed by the EU before and after the agreement were analyzed, using summary measures, such as weighted averages and simple averages, as well as measures of dispersion, such as the standard deviation. In addition, the work was based on the value of EU imports from Mercosur in 2019, to make an analysis together with the mentioned tariffs, and the tariff quotas that are also part of the tariff elimination offer. From this analysis, it was found that the agreement will bring possible gains in market access by Mercosur countries when considering products that currently have high tariffs, however, these effects will not be immediate, as the agreement has a very long exemption period of up to 10 years. For the tariff quotas offered, the results are different from each other, some products will have possible market gains, such as Poultry Meat and Honey, and others will not have so significantly, such as Beef. In conclusion, the agreement will also bring other effects outside the commercial sphere, solidifying more modern legal, technical and environmental structures in Mercosur countries.
The Mercosur-EU trade agreement: an analysis of access to the European market
Keywords: Acordos comerciais; Mercosul; União Europeia; Acesso a mercados; Trade agreements; Mercosur; European Union; Market access; CIENCIAS SOCIAIS APLICADAS::ECONOMIA